Performance and mechanism of ether-based binder (KH-PE) in electrochemically switched ion exchange lithium extraction from salt lake brine with high Mg/Li ratio - Tianyu Feng; Qian Xu; Beichen Sun; Yulong Zhang; Can Wang; Xiao Du; Yongguo Li; Fengfeng Gao; Xiaogang Hao (Journal of Environmental Chemical Engineering, 2026)

Integrating intermittent ultrasound with micro-nanobubbles for enhanced reduction of pathogenic bacteria during fresh-cut lotus root sanitation - Zhiling Shi; Beichen Jiang; Xingxing Gao; Hongchao Zhang (Food Research International, 2026)

Substrate source and mineral protection synergistically govern the temperature response of lake sediment organic carbon - Beichen Wang; Xiaoxi Sun; Zhen Yang; Xinyi Li; Min Cai; Bingfu Yao; Li Liu; Tianran Sun; Jian Yang; Jibin Han; Xiying Zhang; Jianping Wang; et al. (Geochimica et Cosmochimica Acta, 2026)

Highly efficient single-layer color-tunable QLEDs enables by the real-time interface exciplex modulation with AgInZnS QDs - Tianjun Hu; Xiuting Wu; Qingsong Shan; Xingxing Duan; Xiaoyue Cai; Mengjin Huang; Junhui Dai; Hong Zhong; Beichen Yuan; Hengyang Xiang; Linxiang Yang; Qiangyu Dai; et al. (Science Bulletin, 2026)

Coal Permeability Evolution Under True Triaxial Principal Stress and Pore Pressure Competition - Zhaoyang Gong; Dongming Zhang; Beichen Yu; Chongyang Wang; Chenxi Liu (Natural Resources Research, 2026)

Deformation-Fracture Behavior and Permeability Evolution of Coal Under In Situ True Triaxial Stress–Pore Pressure Unloading - Beichen Yu; Dongming Zhang; Yingke Liu; Changbao Jiang; Yubing Liu; Chao Liu; Man Yuan (Rock Mechanics and Rock Engineering, 2026)

Research on the damage laws and failure characteristics of sandstone in coal seam roofs under different rich-water conditions - Yu Chen; Man Wang; Dongming Zhang; Beichen Yu; Ziyang Xiong; Wenzhuo Li (Bulletin of Engineering Geology and the Environment, 2026)

In-situ passivation of Cu and Zn in dyeing sludge incineration ash: Neglected role of the sulfur cycle - Beichen Du; Yuting He; Qinyuan Zhang; Jianran Ye; Xiao Hu; Chuqi Ye; Yuchi Chen; Siwei Liu; Jia Hu; Teng Wang (Journal of Environmental Chemical Engineering, 2025)

Microscopic changes and quantitative prediction of wax content in the peel of Korla fragrant pear at different picking maturities - Yuanyuan Liu; Zhengbao Long; Tongzhao Wang; Zhijuan Zhang; Zhanshuai Dong; Beichen Zhang; Shupeng Dong; Siyu Li (Food Chemistry, 2025)

Exploring the molecular mechanism of Epichloë gansuensis in enhancing the tolerance of Achnatherum inebrians to nitrogen deficiency stress - Ronggui Liu; Hanwen Zhang; Beichen Wang; Jie Jin; Chao Xia; Kamran Malik; Yang Yang; Rong Zheng; Chao Wang; Jianfeng Wang (Mycological Progress, 2025)

Antagonistic effect of changing salinity and dissolved organic carbon on N2O production via different pathways in saline lakes - Xiaoxi Sun; Beichen Wang; Jian Yang; Hui Yu; Bingfu Yao; Mingxian Han; Shenyan Dai; Teng Wen; Jibin Han; Xiying Zhang; Jinbo Zhang; Hongchen Jiang (Water Research, 2025)

The SDGSAT-1 mission and its role in monitoring SDG indicators - Huadong Guo; Changyong Dou; Dong Liang; Bihong Fu; Hongyu Chen; Ziming Zou; Peng Huang; Xiaoming Li; Fansheng Chen; Chengshan Han; Juanjuan Jing; Tai Hu; et al. (Remote Sensing of Environment, 2025)

LLTO-based electrodes for selective lithium extraction from high Mg2+/Li+ brines: Performance and mechanistic insights - Ran Zhang; Jialu Chen; Qian Xu; Beichen Sun; Xiao Du; Shanxia Luo; Xiaogang Hao (Journal of Environmental Chemical Engineering, 2025)

Substrate chemistry trumps mineral protection in governing temperature sensitivity of organic carbon mineralization in saline lake sediments - Beichen Wang; Xiaoxi Sun; Zhen Yang; Xinyi Li; Bingfu Yao; Min Cai; Tianran Sun; Jian Yang; Jibin Han; Xiying Zhang; Hongchen Jiang (Geochimica et Cosmochimica Acta, 2025)

Genetic programming modeling for Cr-contaminated soil remediation by composite cathode displacement - Qiu Yu; Yi Zheng; Liang Zhang; Zao Jiang; Beichen Yu (Process Safety and Environmental Protection, 2025)

High-capacity superlattice La0.55Sm0.20Mg0.25Ni3.27Al0.01 hydrogen storage alloys with series of (A7B23) -(A2B7)1- (x = 0, 0.1, 0.9) structures for nickel-metal hydride batteries - Ning Zhang; Beichen Zhao; Wenfeng Wang; Anyi Zhang; Qiuyue Jia; Yuan Li; Lu Jian; Tianzi Li; Shumin Han; Lu Zhang (Chemical Engineering Journal, 2025)

Antimicrobial capacity of rare earth-doped ZnO composite coating and its influence on fresh orange shelf life quality - Yuqin Lei; Beichen Jiang; Jingchun Hao; Hongchao Zhang (Food Packaging and Shelf Life, 2025)

Characterizing a complex buildup in the Pearl River Mouth Basin of the northern South China Sea: an interplay of carbonates and igneous rocks - Beichen Chen; Leyi Xu; Baojun Liu; Lili Zhang; Dong Xiao; Ya Gao; Feng Wu; Xueqi Yang; Yaming Zou; Yongkun Ma; Yinglin Zhang (Frontiers in Marine Science, 2025)
Volcanic mounds and carbonate buildups share similar geometries, making their differentiation in seismic data a significant challenge. This challenge is further compounded in complex buildups composed of both multi-stage developed igneous rocks and biogenic carbonates. To address this gap, this study investigates a mixed carbonate-igneous buildup at the central of the Baiyun Sag in the northern South China Sea. By analyzing the lithofacies of the carbonates and igneous rocks, the morphological features and spatial distribution patterns corresponding to these sedimentary and volcanic facies were identified. Well-to-seismic calibration was used to delineate the stratigraphic units, and typical seismic profiles of the buildup were analyzed. Eight distinct seismic facies were identified for carbonates and igneous rocks. The evolution of the buildup is divided into three stages: (1) volcanic eruptions and carbonates development, (2) overflowing magma and reef shoal deposits, and (3) reef-bank deposition accompanied by igneous intrusion. We propose that volcanic rocks can be distinguished from carbonates by the temporal and spatial coupling of typical features: (a) surface volcanic rocks and subsurface intrusive bodies are inseparable, with igneous rocks identifiable through faults and volcanic conduits; (b) carbonates typically display symmetrical structures on both sides of the highland and exhibit better stratification away from igneous activity; (c) carbonates generally show a convex clinoform and steep slope at the platform margin, while volcanic mounds exhibit concave gentle slopes. Furthermore, the analysis of high-quality reservoir development within the complex buildups is instrumental for advancing oil and gas exploration in volcanic seamounts and carbonate buildups.

Evaluation of Himawari-8/AHI land surface reflectance at mid-latitudes using LEO sensors with off-nadir observation - Beichen Zhang; Kazuhito Ichii; Wei Li; Yuhei Yamamoto; Wei Yang; Ram C. Sharma; Hiroki Yoshioka; Kenta Obata; Masayuki Matsuoka; Tomoaki Miura (Remote Sensing of Environment, 2025)

A web-based tool for watershed delineation considering lakes and reservoirs - Beichen Zhang; Junzhi Liu; Bin Zhang; Dawei Xiao; Min Chen (Environmental Modelling & Software, 2025)

Microbial difference and its influencing factors in ice-covered lakes on the three poles - Min Cai; Beichen Wang; Jibin Han; Jian Yang; Xiying Zhang; Xiangyu Guan; Hongchen Jiang (Environmental Research, 2024)

Holocene sedimentary distribution and morphological characteristics reworked by East Asian monsoon dynamics in the Mekong River shelf, South Vietnam - Xiao Wang; Wenyan Zhang; Xinong Xie; Hui Chen; Beichen Chen (Estuarine, Coastal and Shelf Science, 2024)

Acoustic emission noise reduction: A case of a uniaxial compression test of gypsum-like rock - Chongyang Wang; Dongming Zhang; Ziyang Xiong; Beichen Yu; Xiaolei Wang; Fake Ren; Yu Chen (International Journal of Rock Mechanics and Mining Sciences, 2024)

High-sensitive determination of tetracycline antibiotics adsorbed on microplastics in mariculture water using pre-COF/monolith composite-based in-tube solid phase microextraction on-line coupled to HPLC-MS/MS - Jinling Pang; Hongzhe Chen; Huige Guo; Kunning Lin; Shuyuan Huang; Beichen Lin; Yuanbiao Zhang (Journal of Hazardous Materials, 2024)

Zero-valent iron in phosphate removal: Unraveling the role of particle size and dissolved oxygen - Shiteng Feng; Beichen Zhang; Jingshu Wang; Jinhui Jeanne Huang (Journal of Water Process Engineering, 2024)

Design and Experimental Study of 50 kW Ocean Thermal Energy Conversion Test Platform Based on Organic Rankine Cycle - Beichen Lu; Yanjun Liu; Xiaoyu Zhai; Li Zhang; Yun Chen (Journal of Marine Science and Engineering, 2024)
In recent years, clean and renewable energy sources have received much attention to balance the contradiction between resource needs and environmental sustainability. Among them, ocean thermal energy conversion (OTEC), which consists of surface warm seawater and deep cold seawater, can rely on thermal cycling to generate electricity and has great potential in alleviating the energy crisis. In this paper, the design and experiment study of a 50 kW OTEC platform is proposed. Thermodynamic modeling, calculation, optimization, and engineering calibration of the system were carried out, and the thermal efficiency reached 2.63% to meet the power generation demand. Experiments were also carried out by using a heat pump unit to simulate hot and cold seawater environments, and data on the stable operation of the system were obtained, with the grid-connected power reaching 47.5 kW and a thermal efficiency of 2.46%. The accuracy of the design scheme is verified, and the theoretical basis and data support are provided for the practical development and application of ocean thermal energy conversion.

Explainable machine learning for the prediction and assessment of complex drought impacts - Beichen Zhang; Fatima K. Abu Salem; Michael J. Hayes; Kelly Helm Smith; Tsegaye Tadesse; Brian D. Wardlow (Science of The Total Environment, 2023)

The roles of different Fe-based materials in alleviating the stress of Cr(VI) on anammox activity: Performance and mechanism - Beichen Zhang; Jingshu Wang; Shiteng Feng; Jinhui Jeanne Huang; Xiaoyu Han (Chemical Engineering Journal, 2023)

Salinity change induces distinct climate feedbacks of nitrogen removal in saline lakes - Xiaoxi Sun; Ehui Tan; Beichen Wang; Zixuan Gan; Jian Yang; Jibin Han; Xiying Zhang; Shuh-ji Kao; Gary King; Hailiang Dong; Hongchen Jiang (Water Research, 2023)

Coal and rock dynamic disaster prevention and control technology in the large mining face of a deep outburst mine - Jianguo Zhang; Man Wang; Hongwei Zhou; Dongming Zhang; Beichen Yu; Chongyang Wang; Yujie Wang (Frontiers of Earth Science, 2023)

Deformation and Seepage Characteristics of Coal Under True Triaxial Loading–Unloading - Chongyang Wang; Dongming Zhang; Beichen Yu; Shujian Li (Rock Mechanics and Rock Engineering, 2023)

True Triaxial Experimental Study of Anisotropic Mechanical Behavior and Permeability Evolution of Initially Fractured Coal - Yubing Liu; Enyuan Wang; Changbao Jiang; Dongming Zhang; Minghui Li; Beichen Yu; Dong Zhao (Natural Resources Research, 2023)

Biot's Coefficient and Permeability Evolution of Damaged Anisotropic Coal Subjected to True Triaxial Stress - Beichen Yu; Dongming Zhang; Shujian Li; Bin Xu; Chao Liu; Yubing Liu (Rock Mechanics and Rock Engineering, 2023)

Experimental Study of Desorption and Seepage Characteristics of Single Gas and CO2–CH4 Gas Mixture in Coal - Beichen Yu; Dongming Zhang; Bin Xu; Weijing Xiao; Chongyang Wang; Weihang Du (Natural Resources Research, 2022)

Spatio-temporal Distribution Characteristics and Environmental Impact Factors of Lung Cancer Mortality: A Case Study of Yuhui District in Bengbu City, China - Jingjing Tang; Kangkang Gu; Jing Mi; Wenhao Zhang; Yunhao Fang; Yuwei Li; Beichen Wang (Chinese Geographical Science, 2022)

Corrigendum: Sea urchins in acute high temperature and low oxygen environments: The regulatory role of microRNAs in response to environmental stress - Lingshu Han; Yanglei Wu; Pengfei Hao; Beichen Ding; Yuanxin Li; Wenpei Wang; Xianglei Zhang; Chuang Gao; Heng Wang; Luo Wang; Weijie Zhang; Yaqing Chang; et al. (Frontiers in Marine Science, 2022)

Sea Urchins in Acute High Temperature and Low Oxygen Environments: The Regulatory Role of microRNAs in Response to Environmental Stress - Lingshu Han; Yanglei Wu; Pengfei Hao; Beichen Ding; Yuanxin Li; Wenpei Wang; Xianglei Zhang; Chuang Gao; Heng Wang; Luo Wang; Weijie Zhang; Yaqing Chang; et al. (Frontiers in Marine Science, 2022)
Strongylocentrotus intermedius is an economically valuable sea urchin species in China. However, its growth and survival are severely constrained by ocean warming and the hypoxia that often accompanies high water temperatures. MicroRNAs (miRNAs) are important regulators of gene expression in response to environmental change. In this study, high-throughput RNA sequencing was used to investigate changes in miRNA expression in S. intermedius under heat (25°C), hypoxia (2 mg/L O 2 ), and combined heat and hypoxia stresses. Twelve small RNAs libraries were constructed and 17, 14, and 23 differentially expressed miRNAs (DEMs) were identified in the heat, hypoxia, and combined stress groups ( P <0.05), respectively. Gene ontology and Kyoto Encyclopedia of Genes and Genomes pathway functional analyses of putative target genes of the DEMs suggested that these miRNAs were important in basal metabolism, apoptosis, oxidative stress, and immune-related pathways. By co-analysis with published transcriptome data, key DEMs (miR-193, miR-184, miR-133, miR-125, miR-2008) and their key target genes ( EGF3 , ABCB4 , CYCL , PAN2 , CALN ) were identified. Quantitative real-time PCR analysis of the expression of 10 DEMs and their key target genes confirmed the RNA sequencing results. These results provide information on gene expression regulation of the molecular mechanisms underlying the response of S. intermedius to multi-cause environmental stresses.

Top-Down aircraft detection in large-scale scenes based on multi-source data and FEF-R-CNN - Beichen Zeng; Dongping Ming; Fengcheng Ji; Jiawei Yu; Lu Xu; Liang Zhang; Xinyi Lian (International Journal of Remote Sensing, 2022)

An online participatory system for SWMM-based flood modeling and simulation - Beichen Zhang; Min Chen; Zaiyang Ma; Zhuo Zhang; Songshan Yue; Dawei Xiao; Zhiyi Zhu; Yongning Wen; Guonian Lü (Environmental Science and Pollution Research, 2022)

Difference Analysis on Sandstone Permeability After Treatment at Different Temperatures During the Failure Process: A Case Study of Sandstone in Chongqing, China - Weijing Xiao; Dongming Zhang; Haitao Li; Guo Yu; Han Yang; Beichen Yu (Pure and Applied Geophysics, 2021)

Metabolomics analysis for skin ulceration syndrome of Apostichopus japonicus based on UPLC/Q-TOF MS - Yang Zhang; Youquan Wang; Xiaoyu Liu; Beichen Ding; Yi Sun; Yaqing Chang; Jun Ding (Journal of Oceanology and Limnology, 2021)

Mechanical Properties and Failure Behavior of Dry and Water-Saturated Anisotropic Coal Under True-Triaxial Loading Conditions - Yubing Liu; Guangzhi Yin; Minghui Li; Dongming Zhang; Gun Huang; Peng Liu; Chao Liu; Honggang Zhao; Beichen Yu (Rock Mechanics and Rock Engineering, 2020)